Total synthesis of the potent anti-inflammatory natural product solomonamide A along with structural revision and biological activity evaluation - Jachak, Gorakhnath R.; Athawale, Paresh R.; Agarwal, Heena; Barthwal, Manoj Kumar; Lauro, Gianluigi; Bifulco, Giuseppe; Reddy, D. Srinivasa (Organic & Biomolecular Chemistry, 2018)
Herein, we report the total synthesis of solomonamide A along with its structural revision for the first time. The natural product possesses very potent anti-inflammatory activity, and it contains a macrocyclic peptide having four consecutive stereocenters on an unnatural amino acid component. The key features in the present synthesis include the application of an Evans aldol reaction, ligand-free Heck macrocyclization and chemoselective oxidations. The challenging task of fixing the stereochemistry of OH at the C5-position was accomplished with the help of DFT calculations, applying a quantum-mechanical (QM)/NMR combined approach. Biological evaluation in a mouse paw edema model revealed that a low dose (0.3 mg kg(-1)) of the synthesized solomonamide A showed 74% reduction at 6 h, which was comparable to a high dose (10 mg kg(-1)) standard drug dexamethasone effect (75% at 6 h). Thus, we further confirmed the revised structure of solomonamide A.

DFT/NMR approach for the configuration assignment of groups of stereoisomers by the combination and comparison of experimental and predicted sets of data - Lauro, Gianluigi; Das, Pronay; Riccio, Raffaele; Reddy, D. Srinivasa; Bifulco, Giuseppe (Journal of Organic Chemistry, 2020)
Quantum mechanical/nuclear magnetic resonance (NMR) approaches are widely used for the configuration assignment of organic compounds generally comparing one cluster of experimentally determined data (e.g., C-13 NMR chemical shifts) with those predicted for all possible theoretical stereoisomers. More than one set of experimental data, each related to a specific stereoisomer, may occur in some cases, and the accurate stereoassignments can be obtained by combining the experimental and computed data. We introduce here a straightforward methodology based on the simultaneous analysis, combination, and comparison of all sets of experimental/calculated C-13 chemical shifts for aiding the correct configuration assignment of groups of stereoisomers. The comparison of the differences between the calculated/experimental chemical shifts instead of the shifts themselves led to the advantage of avoiding errors arising from calibration procedures, reducing systematic errors, and highlighting the most diagnostic differences between calculated and experimental data. This methodology was applied on a tetrad of synthesized cladosporin stereoisomers (cladologs) and further corroborated on a tetrad of pochonicine stereoisomers, obtaining the correct correspondences between experimental and calculated sets of data. The new MAE(Delta Delta delta) parameter, useful for indicating the best fit between sets of experimental and calculated data, is here introduced for facilitating the stereochemical assignment of groups of stereoisomers.

Phytochemical investigation of Cannabis sativa: Isolation and structure determination of spiroindans - Nalli, Yedukondalu; Komal; Boccia, Eleonora; Lauro, Gianluigi; Bifulco, Giuseppe; Krishna, Gamidi Rama (Journal of Molecular Structure, 2025)
Four undescribed, beta-, alpha-chevicospiranol (1, 2), 4-prenylspirenone B (3), and, 6-prenylspirenone B (4), along with ten known spiroindans were discovered in Cannabis sativa. The structures were determined through 1D, 2D NMR, HRMS, and quantum mechanical calculations. Compounds 1 and 2 have an unprecedented fused system of 3hydroxychavicol with beta- and alpha-cannabispiranol core, respectively, while 3 and 4 are prenylated spiroindan congeners. Detailed NMR data assignments of isomeric pairs 2a - 2b, 3a - 3b, and 4a - 4b, corrected the misidentification of the previously reported spiroindane, prenylspirodinone (5). Besides, the crystal structures of 2a, 3a, and 5a were determined by SC-XRD experiments.
Keywords: Cannabaceae; Cannabis sativa L.; Crystal structure analysis of spiro-indans; Indian cannabis variety; NMR data of spiro-indans; Spiro-indans